A dynamically tunable terahertz metamaterial absorber based on an electrostatic MEMS actuator and electrical dipole resonator array. (6th January 2016) - Hu, Fangrong; Xu, Ningning; Wang, Weiming; Wang, Yue'e; Zhang, Wentao; Han, Jiaguang; Zhang, Weili
Abstract: We experimentally demonstrate a dynamically tunable terahertz (THz) metamaterial absorber based on an electrostatic microelectromechanical systems (MEMS) actuator and electrical dipole resonator array. The absorption of the THz wave is mainly a result of the electrical dipole resonance, which shows a tunable performance on demand. By preforming the finite integral technique, we discovered that the central absorption frequency and the amplitude can be simultaneously tuned by the applied voltage U . Characterized by a white light interferometer and a THz time domain spectroscopy system, our THz absorber is measured to show a modulation of the central frequency and the amplitude to about 10% and 20%, respectively. The experimental results show good agreement with the simulation. This dynamically tunable absorber has potential applications on THz filters, modulators and controllers.